2022
DOI: 10.1186/s13018-022-03222-1
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of falls in the older adults: a comprehensive systematic review and meta-analysis

Abstract: Background With increasing life expectancy, declining mortality, and birth rates, the world's geriatric population is increasing. Falls in the older people are one of the most common and serious problems. Injuries from falls can be fatal or non-fatal and physical or psychological, leading to a reduction in the ability to perform activities of daily living. The aim of this study was to determine the prevalence of falls in the older people through systematic review and meta-analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 94 publications
1
36
2
6
Order By: Relevance
“…Moreover, the risk of hospitalization was also reduced by half, as previously described in a study by Park et al 23 (even though to a lesser extent). Finally, we observed a decreased risk of falling that is associated with a higher risk of death in the scientific literature 30 . Previous cohort studies have suggested an increased risk of mortality in senior housing compared with communities in US 20,21 , Australia 19 or Ireland 22 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, the risk of hospitalization was also reduced by half, as previously described in a study by Park et al 23 (even though to a lesser extent). Finally, we observed a decreased risk of falling that is associated with a higher risk of death in the scientific literature 30 . Previous cohort studies have suggested an increased risk of mortality in senior housing compared with communities in US 20,21 , Australia 19 or Ireland 22 .…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the risk of hospitalization was also reduced by half, as previously described in a study by Park et al 23 (even though to a lesser extent). Finally, we observed a decreased risk of falling that is associated with a higher risk of death in the scientific literature 30 .…”
Section: Discussionmentioning
confidence: 52%
“…Third, we only focused on toxicity‐related hospitalizations and thus our results should be interpreted with caution as we did not include other causes of hospitalizations in this analysis. Fourth, in this cohort, only 12.2% of patients reported a positive fall history, which is a relatively lower proportion than reported in other cohorts of older adults 60–62 . This speaks either to limitations of retrospective recall, as fall history is collected through self‐report, or a possibility that our study did not catch the full extent of the fall history in this study population.…”
Section: Discussionmentioning
confidence: 61%
“…Falls are one of the leading causes of injuries and death in older adults worldwide (Shyamala et al., 2015; World Health Organization, 2021). Globally, the prevalence of falls in older adults above 65 years was reported as 26.5% (Salari et al., 2022). Deficits in gait and balance, polypharmacy, and history of falls are some of the major risk factors for falls in older adults (Ambrose et al., 2013).…”
Section: Introductionmentioning
confidence: 99%